2006
DOI: 10.1038/sj.bjc.6602942
|View full text |Cite
|
Sign up to set email alerts
|

COX inhibitors and breast cancer

Abstract: There is considerable evidence to suggest that prostaglandins play an important role in the development and growth of cancer. The enzyme cyclo-oxygenase (COX) catalyses the conversion of arachidonic acid to prostaglandins. In recent years, there has been interest in a possible role for COX inhibitors in the prevention and treatment of malignancy. Cyclo-oxygenase-2 (COX-2) is overexpressed in several epithelial tumours, including breast cancer. Preclinical evidence favours an antitumour role for COX inhibitors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
107
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(111 citation statements)
references
References 26 publications
2
107
0
2
Order By: Relevance
“…COX-2 inhibitors, which unlike COX-1 inhibitors do not increase the risk of bleeding, are used as pain relievers during surgery (47) and have been used for the prevention and treatment of malignancies (48). Furthermore, in a previous study we found that COX-2, but not COX-1 inhibition, attenuated the metastasis-promoting effects of surgery, and etodolac was more effective than the highly COX-2 selective celecoxib (22).…”
Section: Sectionmentioning
confidence: 99%
“…COX-2 inhibitors, which unlike COX-1 inhibitors do not increase the risk of bleeding, are used as pain relievers during surgery (47) and have been used for the prevention and treatment of malignancies (48). Furthermore, in a previous study we found that COX-2, but not COX-1 inhibition, attenuated the metastasis-promoting effects of surgery, and etodolac was more effective than the highly COX-2 selective celecoxib (22).…”
Section: Sectionmentioning
confidence: 99%
“…For those women who present with tumors with positive hormone receptors, the use of aspirin could contribute to the suppression of aromatase activity, reducing the intra-mammary prostaglandin production, and thus, estrogen production (59). In particular, it has been shown that E2 prostaglandin (PGE 2 ) stimulates the transcription of aromatase, increasing the estrogen levels and, moreover, contributing to the progression of estrogen-dependent BC (60). The induction and overexpression of COX-2 and its main product PGE 2 in human mammary tissue, have also been associated with aromatase-catalyzed estrogen biosynthesis (61).…”
Section: Aspirin Mechanisms Of Actionmentioning
confidence: 99%
“…Maspin protein is a tumor-suppressor serine protease, which is expressed in several tissues including mammary epithelia, prostate, epidermis, lung, and in the stromal cells of the cornea (35,36,61,62). This protein is of special interest as it is able to inhibit cellular invasion and metastasis and to act as a tumor suppressor (37,60).…”
Section: Aspirin As An Inhibitor Of Metastasismentioning
confidence: 99%
“…17 A growing body of experimental and epidemiological evidence suggests that the use of NSAIDs may decrease the incidence of mammary cancer, tumor burden, and tumor volume. [18][19][20] Although this effect has been studied within the past few decades, the mechanism by which these benefits occur is unclear. Nimesulide [N-(4-nitro-2-phenoxyphenyl) methane sulfonamide] is a nonsteroidal anti-inflammatory drug with a preferential cyclooxygenase-2 inhibitory activity and has been available in some Asia and European countries since 1985.…”
Section: Introductionmentioning
confidence: 99%